Preventing antimalarial drug resistance through combinations. - White, N (1998)
Throughout the tropical world antimalarial drug resistance is increasing, particularly in the potentially lethal malaria parasite Plasmodium falciparum. In some parts of Southeast Asia, parasites which are resistant to chloroquine, pyrimethamine-sulfadoxine, and mefloquine are prevalent. The characteristics of a drug that make it vulnerable to the development of resistance are a long terminal elimination half-life, a shallow concentration-effect relationship, and that one or two base-pair mutations confer a marked reduction in susceptibility. The development of resistance can be delayed or prevented by drug combinations. The artemisinin derivatives are the most potent of all antimalarial drugs. They reduce the infecting parasite biomass by approximately 10 000-fold per asexual life cycle. There are good arguments for combining, de novo, an artemisinin derivative with all newly introduced antimalarial drugs.